Effect of different skin suits on speed skating performance - Oggiano, L.; Saetran, L. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
Drag in speed skating is the most important frictional loss. This paper presents a numerical and experimental investigation on how rough textiles are able to affect the drag in competition speed skating suits. The attention has been mostly focused on the legs of the athletes. Methods: Experiments with a doll in scale 1:1 have been carried out. Drag at different speeds (from 4m/s to 17m/s) has been acquired and Cd-Speed curves for each suit have been plotted. A mathematical model based on the balance between the power generated and the power spent by the athletes has been used in order to estimate the final time in a 1500m long track competition for women and men. Results: Speed skating suits do affect speed skaters performances. A maximum difference in drag of about 10% has been acquired and a maximum difference in final time of about 3s has been estimated. Rough textiles on the suits legs are able to reduce the drag at low speeds (V<11m/s) but negatively affects performances at high speed (V>13m/s).